Growth and biomass production of prickly pear in the second cycle irrigated with treated domestic sewage (Bioscience Journal, 2020)
This study aimed to evaluate, in the second cycle, the growth and production of ‘Orelha-de-elefante Mexicana’ prickly pear (Opuntia sp.) under complementary irrigation with treated domestic sewage. The experiment was carried out in the Milagre Settlement, municipality of Apodi-RN, Brazil, from June 2016 to February 2017. Five treatments were evaluated, corresponding to four irrigation frequencies (2.3, 7.0, 14.0 and 21.0 days) to apply an effluent depth of 3.5 mm, and the control, rainfed cultivation (without irrigation). The experimental design was randomized blocks, with four replicates. After preliminary-primary treatment, the domestic sewage showed acceptable chemical and physical characteristics for fertigation under the conditions adopted in the prickly pear cultivation. 234 days after the 1st cut in the plants, the following morphometric characteristics were measured: plant height and length, width, perimeter, thickness and number of primary and secondary cladodes, and biomass accumulation. Complementary irrigation with treated domestic sewage effluent applied at intervals of 2.3, 7.0, 14.0 and 21.0 days allowed satisfactory growth and production of ‘Orelha-de-elefante Mexicana’ prickly pear; without irrigation, its development was substantially hampered during the dry period. Complementary irrigation with 3.5 mm of domestic sewage effluent applied at intervals of 2.3, 7.0 and 14.0 days led to highest growth and biomass accumulation in ‘Orelha-de-elefante Mexicana’ prickly pear.